Alterations in Protein Expression Caused by the hha Mutation in Escherichia coli: Influence of Growth Medium Osmolarity - Balsalobre, Carlos (American Society for Microbiology, 1999)
The Hha protein belongs to a new family of regulators involved in the environmental regulation of virulence factors. The aim of this work was to study the effect of the hha mutation on the overall protein pattern of Escherichia coli cells by two-dimensional polyacrylamide gel electrophoresis. The growth medium osmolarity clearly influenced the effect of the hha mutation. The number of proteins whose expression was altered in hha cells, compared with wild-type cells, was three times larger at a high osmolarity than at a low osmolarity. Among the proteins whose expression was modified by the hha allele, both OmpA and protein IIA(Glc) of the phosphotransferase system could be identified. As this latter enzyme participates in the regulation of the synthesis of cyclic AMP and hence influences the catabolite repression system, we tested whether the expression of the lacZ gene was also modified in hha mutants. This was the case, suggesting that at least some of the pleiotropic effects of the hha mutation could be caused by its effect on the catabolite repression system.